The Relationship Between Socioeconomic Status and Beverage Consumption in Children: The Cuenca Study [Relación Entre el Estatus Socioeconómico y el Consumo de Bebidas en Niños: Estudio de Cuenca] - Garcia-Hermoso, A (Grupo Aula Medica S.A., 2018)
Introduction: beverage consumption constitutes a source of children’s daily energy intake. Some authors have suggested that consumption of caloric beverages is higher in children with a low socioeconomic position because families limit their spending on healthy food in order to save money. Objective: the aim of this study was to explore the relationship between socioeconomic status and Spanish children’s beverage consumption. Methods: a cross-sectional study was conducted in a sub-sample of 182 children (74 girls) aged 9-11 from the province of Cuenca (Spain). Beverage consumption was assessed using the YANA-C assessment tool, validated for HELENA study. Data for parental socioeconomic status were gathered by using self-reported occupation and education questions answered by parents and classified according to the scale proposed by the Spanish Society of Epidemiology. Results: beverage intake was higher in children belonging to a middle-status family than in those of upper socioeconomic status (p = 0.037). The energy from beverages was similar in most water intake categories, except for water from beverages (p = 0.046). Regarding other beverages categories, middle-status children had higher consumption levels. In contrast, lower status children drank more fruit juices and skimmed milk. All of these do not show statistically significant differences. Conclusions: our study did not find significant associations between beverages consumption and socioeconomic status in children. In fact, intake for most beverage categories was higher in middle-status children than in both other socioeconomic groups. Future research is needed in order to identify this complex relation between socioeconomic inequality and beverage intake behavior. © 2018 SENPE y Arán Ediciones S.L.